Evaluation of feedlot performance, carcass characteristics, carcass retail cut distribution, Warner-Bratzler shear force, and fatty acid composition of purebred Jersey and crossbred Jersey steers - Jaborek, Jerad R (Transl Anim Sci, 2019)
Feedlot performance, carcass yield, fatty acid composition, and tenderness of crossbred Jersey steers compared with purebred Jersey steers was investigated. Purebred Jersey (n = 21) and crossbred Jersey steers sired by Angus (n = 9), SimAngus (n = 10), and Red Wagyu (n = 15) bulls were assessed. Adjusted to a common initial body weight (BW), crossbred Jersey steers had a greater rate of BW gain (P ≤ 0.01) compared with purebred Jersey steers. Angus sired steers had a greater daily dry matter intake (P ≤ 0.01) compared with Wagyu and Jersey sired steers, whereas SimAngus sired steers had a greater daily dry matter intake compared with Jersey sired steers. Wagyu sired steers were more feed efficient (P ≤ 0.03) compared with Jersey sired steers. Even with a greater (P ≤ 0.01) number of days on feed, off-test BW of purebred Jersey steers was less (P ≤ 0.01) compared with crossbred Jersey steers. Adjusted to a common hot carcass weight, Angus sired steers had a greater backfat thickness (P ≤ 0.01) compared with steers from the other sire breeds. Kidney fat percentage (P ≤ 0.01) was greatest for Jersey sired steers, with SimAngus and Wagyu sired steers being intermediate, and the lowest for Angus sired steers. Carcasses from Angus and Wagyu sired steers had a greater marbling score (P ≤ 0.03) compared with carcasses from Jersey sired steers. Carcasses from Wagyu sired steers had a greater (P ≤ 0.01) total red meat yield compared with Angus and Jersey sired steers, whereas SimAngus sired steers had a greater total red meat yield compared with Jersey sired steers. Carcasses from Angus sired steers tended (P = 0.07) to have a greater percentage of fat trim compared with Wagyu sired steer carcasses. There were no sire breed differences (P = 0.38) for the percentage of total bone from the carcasses. Tenderness, measured by Warner-Bratzler shear force (WBSF), was improved (P ≤ 0.01) with 14 d of postmortem aging compared with 7 d. Wagyu and SimAngus sired steers produced steaks with a lesser (P ≤ 0.01) WBSF compared with steaks from Angus and Jersey sired steers. Steaks from Angus sired steers tended (P = 0.10) to have a greater percentage of total lipid and had a greater (P ≤ 0.05) percentage of 16:0 compared with steaks from Jersey sired steers. Overall, crossbred Jersey steers improved economically relevant production parameters of feedlot performance, carcass quality, carcass yield, and instrumental predictors of eating quality compared with purebred Jersey steers.